The Footprint of Atlantic Multidecadal Oscillation on the Intensity of Tropical Cyclones Over the Western North Pacific - Sun, Cheng; Liu, Yusen; Gong, Zhanqiu; Kucharski, Fred; Li, Jianping; Wang, Qiuyun; Li, Xiang (Frontiers in Earth Science, 2020)
SST over the western North Pacific (WNP) exhibits strong decadal to multidecadal variability and in this region, warm waters fuel the tropical cyclones (TCs). Observational records show pronounced decadal variations in WNP TC metrics during 1950-2018. Statistical analysis of the various TC metrics suggests that the annual average intensity of WNP TCs is closely linked to the AMO (r = 0.86 at decadal timescales, p < 0.05). Observations and coupled atmosphere-ocean simulations show that the decadal WNP SST variations regarded as the primary driver of TC intensity, are remotely controlled by the AMO. Corresponding to the WNP SST warming, the local SLP gets lower and the tropospheric air becomes warmer and moister, enhancing atmospheric instability and the generation of convective available potential energy. These favorable changes in the background environment provide more “fuel” to the development of deep convection and intensify the WNP TCs. The footprints of AMO in WNP SST and atmospheric states through trans-basin interaction eventually exert a significant impact on the TC intensity over the WNP region.